Relationship of thyroid gland elasticity with age, gender and thyroid gland volume in the shear-wave ultrasound elastography - Urfalı, Furkan Ertürk; Erarslan, Sertaç; Özkul, Bahattin; Korkmaz, Mehmet; Tok, Sermin (The European Research Journal, 2022)
Objectives: The aim of the study is to determine the correlation between thyroid gland elasticity with thyroxine, thyroid-stimulating hormone levels, age, gender and thyroid gland volume in the normal population. Methods: The study was conducted with 105 healthy cases. Thyroid gland elasticity was evaluated in axial plan using ultrasonography. Results: The relationship between thyroid gland elasticity and thyroxine, thyroid-stimulating hormone levels, age, gender and thyroid gland volume was evaluated. The mean thyroid gland volume was 11.95 ± 9.23 mm3. A moderate negative correlation was found between thyroid gland volume and kPa value observed from the elastography examination. A moderate negative correlation was found between elastography kPa value and blood thyroxine level. No correlations were found between thyroid-stimulating hormone level, age, gender and thyroid gland elasticity. Conclusions: The negative correlation between thyroid gland volume and thyroxine level with thyroid gland elasticity should be considered in elastographic evaluations.